Gingival crevicular fluid level of receptor activator nuclear factor - kappa - B ligand (RANKL) in insulin dependant diabetes mellitus patients - Heba Mohamed Tawfik Abdelfattah; Olfat Gamal Shaker; Shahira Gamal Elashiry (Cairo : Heba Mohamed Tawfik Abdelfattah, 2011)
RANKL is a key mediator in the process of osteoclast formation . This membrane - bound protein is a member of the tumor necrosis factor super - family , the purpose of the present study was to assess the level of (RANKL) in samples of gingival crevicular fluid in insulin dependent diabetes mellitus Patient suffering from chronic periodontitis and to compare it with chronic periodontitis patients and healthy controls
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral (Diagnosis)
Issued also as CD
Keywords: Bleeding on probing; Bone mineral density; Diabetes mellitus